2009
DOI: 10.2166/wh.2009.070
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Helicobacter pylori and the role of water and biofilms

Abstract: Documented evidence relating to the survival of Helicobacter pylori outside the gastric niche is extremely limited. To date the primary transmission routes of H. pylori have yet to be confirmed and when this is achieved preventive infection control measures can be implemented to reduce and ultimately prevent human infection from this pathogen. There is mounting evidence which suggests that the prevalence of H. pylori infection has a strong correlation with access to clean water, suggesting a transmission route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
1
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 96 publications
1
36
1
9
Order By: Relevance
“…Biofilms within water distribution systems in particular are thought to be diverse microbial communities and potential reservoirs of disease-causing organisms in the indoor environment. Several pathogens including Escherichia coli, Legionella pneumophila (10-13), Vibrio cholerae (14), and Helicobacter pylori (15,16) have been detected in biofilms within water distribution systems. A recent 16S rRNA gene (abbreviated henceforth as 16S unless otherwise stated) molecular survey also revealed significant loads of Mycobacterium avium in showerhead biofilms (17).…”
mentioning
confidence: 99%
“…Biofilms within water distribution systems in particular are thought to be diverse microbial communities and potential reservoirs of disease-causing organisms in the indoor environment. Several pathogens including Escherichia coli, Legionella pneumophila (10-13), Vibrio cholerae (14), and Helicobacter pylori (15,16) have been detected in biofilms within water distribution systems. A recent 16S rRNA gene (abbreviated henceforth as 16S unless otherwise stated) molecular survey also revealed significant loads of Mycobacterium avium in showerhead biofilms (17).…”
mentioning
confidence: 99%
“…Biofilms in drinking water distribution systems have been reported as possible reservoirs of H. pylori and attempts to culture these cells from water samples have proven unsuccessful (Linke et al, 2010;Percival and Thomas, 2009). Due to the fastidious nature of this bacterium, the lack of standard culture methods for environmental samples, and the controversy in its ability to survive in an infectious state in the environment, very few quantitative studies have been reported (Percival and Thomas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fastidious nature of this bacterium, the lack of standard culture methods for environmental samples, and the controversy in its ability to survive in an infectious state in the environment, very few quantitative studies have been reported (Percival and Thomas, 2009). Legionella pneumophila is a ubiquitous bacterium in natural aquatic environments that can also persist in humancontrolled systems containing water, such as air conditioning and plumbing infrastructures (Steinert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Infection is usually acquired in childhood and primarily may spread from person to person via the faecal-oral route (Roosendaal et al 1993;Brown 2000). The precise route and mode of transmission of H. pylori is unknown but studies advocate that the natural reservoir of H. pylori outside the human gastrointestinal niche is ground water, surface water and drinking water (Hegarty et al 1999;Giã o et al 2008;Percival & Thomas 2009). It is also observed that H. pylori can also cause natural infection in other primates (Goodman & Correa 1995;Westblom et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between the bacterium aggressive factors and the host defence mechanisms may lead to duodenal ulcers, chronic gastritis and stomach cancer (Coghlan et al 1987;Graham & Yamaoka 1998;Passaro et al 2002). The risk of H. pylori infection is high in developing countries (Al-Moagel et al 1990) while the prevalence of H. pylori in developed countries is low due to better industrialization, public health measures/ education and living conditions (Bardhan 1997;Percival & Thomas 2009). It is observed that the municipal drinking water supplies are the source for H. pylori infection especially in developing countries, which may be due to contaminated water supplies (Klein et al 1991;Brown 2000;Baker et al 2002;Lu et al 2002;Giã o et al 2008).…”
Section: Introductionmentioning
confidence: 99%